The utility of thrombophilia and hematologic screening in live liver donation. Issue 1 (6th December 2020) - Naymagon, Leonard; Tremblay, Douglas; Facciuto, Marcelo; Lapointe Rudow, Dianne; Schiano, Thomas
Abstract: Background: Most centers perform some degree of hematologic screening, including thrombophilia testing, on prospective live liver donors. The nature and extent of such screens are not standardized, and there is limited evidence regarding hematologic risk stratification. Methods and Results: We present an experience of hematologic screening among prospective liver donors. Five‐hundred‐eightyfour patients were screened for liver donation between 1/2013 and 1/2020, of whom 156 (27%) proceeded to donor hepatectomy. Thirty‐three of 428 (8%) declined patients were excluded for hematologic indications. Hematologic indications were the 2nd most frequent medical indications for exclusion (trailing only hepatologic indications). The most common reason for hematologic exclusion was concern regarding thrombophilia. Nevertheless, 21 patients with evidence of possible thrombophilia proceeded to donor hepatectomy, and none incurred hematologic complications. Similarly, seven patients with screening findings concerning for increased bleeding risk (most often thrombocytopenia) underwent donor hepatectomy without hematologic complication. Three of 156 (2%) of patients who underwent donor hepatectomy incurred a hematologic complication (all thrombotic, none fatal). None of these patients had any evident hematologic risk factor on screening. Conclusion: This study underscores the difficulty of hematologic risk stratification among prospective living donors, however, suggests that some patients with relatively mild risk factors may be safe for donation.